1997
DOI: 10.1172/jci119234
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between interleukin-5 and eotaxin in regulating blood and tissue eosinophilia in mice.

Abstract: The mechanism of cooperation between IL-5 and eotaxin for the selective accumulation of eosinophils at sites of allergic inflammation is unknown. In this investigation we have used IL-5 deficient mice to define the relationship between this cytokine and eotaxin in the regulation of blood eosinophilia and eosinophil homing and tissue accumulation. Both IL-5 and eotaxin could independently induce a rapid and pronounced blood eosinophilia in wild type mice when administered systemically. In contrast, only eotaxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
263
0
9

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 326 publications
(289 citation statements)
references
References 33 publications
17
263
0
9
Order By: Relevance
“…However, we have shown for the first time that the presence of a blood eosinophilia, induced by the sensitization protocol, is insufficient to support the cellular responses to eotaxin: injection of eotaxin into dorsal air-pouches of sensitized mice failed to induce an E influx but the same concentration of the chemokine was active in the peritoneal cavity, confirming our previous study [10]. It has been shown that administration of high doses of eotaxin into murine skin reduces the extent of E recruitment [12]. Therefore, in this study, lower doses of eotaxin were administered into air-pouches but again no E recruitment was elicited.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…However, we have shown for the first time that the presence of a blood eosinophilia, induced by the sensitization protocol, is insufficient to support the cellular responses to eotaxin: injection of eotaxin into dorsal air-pouches of sensitized mice failed to induce an E influx but the same concentration of the chemokine was active in the peritoneal cavity, confirming our previous study [10]. It has been shown that administration of high doses of eotaxin into murine skin reduces the extent of E recruitment [12]. Therefore, in this study, lower doses of eotaxin were administered into air-pouches but again no E recruitment was elicited.…”
Section: Discussionsupporting
confidence: 84%
“…This was in contrast to the pronounced E migration observed after eotaxin injection into the peritoneal cavity of these mice [10]. Overall these studies are in agreement with reports showing that eotaxin is more effective in recruiting E s in the presence of increased numbers of circulating E s [11,12] but they also indicated that increased numbers of circulating E s per se is insufficient to obtain a cellular response to eotaxin administration.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Animal experimental studies lend considerable credence to the notion that eotaxin plays a pivotal role in eosinophil recruitment in allergic inflammation (Gonzalo et al, 1996(Gonzalo et al, , 1998Mould et al, 1997). These studies also provide support for the regulation of eotaxin expression by so-called Th2 cytokines, notably interleukin-13 (IL-13) (Li et al, 1999;Teran et al, 1999;Zhu et al, 1999).…”
mentioning
confidence: 86%